PENGUATAN PENDIDIKAN KARAKTER MELALUI PEMBELAJARAN PPKn - Raditiya Niko Widi Pratama; Aneyla Camaliya Audrey Afandie; Nuria Elsa Aulia; Bunga Ericia Putri Rifanda (Prosiding Konferensi Ilmiah Dasar, 2026)
One of the key tenets of Indonesia's national education system is character education, which attempts to mould the country's future generation to have noble character, reflect the Pancasila spirit, and be able to coexist peacefully in society. In addition to describing the role of the instructor, the creation of instructional materials, and their relationship to the development of students' social attitudes, this research attempts to analyse the application of character education reinforcement in Civics Education (PPKn) learning. Ten relevant literary sources are subjected to content analysis as part of the library research technique. The results show that students' social views are positively impacted by the incorporation of character education into civics education, which is bolstered by character-rich instructional materials and the active engagement of the instructor. The implementation of Pancasila ideals in school life is reinforced by the policy guidance provided by the Pancasila Student Profile. According to the study's findings, policy, educators, instructional resources, and the school setting must work together for character education to be successful.